Tax Revenue, Total Expense, Gross Domestic Production and Budget Deficit: A Study in Sri Lanka - Anojan, V. (Accounting and Finance Research, 2018)
The main aim of this study is to find out relationship among tax revenue, total expense, gross domestic production and budget deficit of Sri Lanka from 1990 to 2015. Budget deficit is a vital problem in Sri Lanka. This research mainly considers three independent variables such as tax revenue, total expense and gross domestic production and budget deficit is dependent variable of this research. Data of this study collected from annual report, ministry of finance and central bank reports of Sri Lanka. Descriptive and inferential statistics were performed with the help of SPSS to analyze research data, answer research questions, reach research objectives and test hypothesis in this study. Correlation analysis confirmed that there are positive significant relationship between direct tax revenue and gross domestic production (98.4%), direct tax revenue and budget deficit (98.6%), indirect tax revenue and gross domestic production (99.2%), indirect tax revenue and budget deficit (98.5%), capital expense and gross domestic production (99.3%), capital expense and budget deficit (98.5%), recurrent expense and gross domestic production (98.7%), recurrent expense and budget deficit (99.3%), gross domestic production and budget deficit (97.2%) of Sri Lanka from 1990 to 2015. Regression analysis confirmed that 98.9% of gross domestic production depends on capital expense, recurrent expense, direct tax revenue and indirect tax revenue of the Sri Lanka. Capital expense has significant impact on the gross domestic production of the country (P = 0.024). 99.4% of budget deficit depends on capital expense, recurrent expense, direct tax and indirect tax of Sri Lanka. Further it can be stated that indirect tax revenue and recurrent expense have significant impact on the budget deficit of Sri Lanka (P < 0.05). This study concludes that there is possibility to change budget deficit and gross domestic production through capital expense, recurrent expense, direct tax revenue and indirect tax revenue in Sri Lanka.
Keywords: tax revenue; recurrent expense; capital expense; gross domestic production